Soft Power- Track Two Diplomacy: Insights into Nepal-Japan Relations - Adhikari, Jyoti (Intellectual Journal of Academic Research, 2024)
The study delves into the cultural exchanges and historical context that have shaped these ties, particularly emphasizing the role of Buddhist Sanskrit scriptures. A key figure in this narrative is Rev. Ekai Kawaguchi, a Japanese Buddhist monk whose efforts in the late 19th and early 20th centuries exemplify the principles of scripture diplomacy and soft power. The primary aim is to analyze how Kawaguchi’s activities contributed to enhancing Nepal-Japan relations and to draw broader implications for soft power diplomacy in contemporary international relations. The article employs qualitative analysis, examining historical documents, cultural exchanges, and the impact of educational initiatives on diplomatic relations. The results underscore the significance of cultural and educational interactions in fostering and sustaining diplomatic relations. Kawaguchi’s contributions highlight the potential of soft power as a diplomatic tool, suggesting that cultural diplomacy can effectively strengthen bilateral ties. This study provides valuable insights into the role of soft power diplomacy in modern international relations, particularly through the lens of Japan and Nepal’s historical connections. It emphasizes the importance of educational and cultural exchanges in building and maintaining diplomatic relationships.